Problems and prospects of co- operative marketing of handicraft products with special reference to wood and metal products - Vanaja Menon (Faculty of Agriculture, College of Co-operation and Banking, 1990)
Study on “Problems and prospects of co – operative Marketing of Handicrafts Product with special reference to wood and Metal Products” has been carried out to identify channels of distribution of wood and metal handicrafts products, to measure the efficiency of distribution channels, to assess the extent of assistance given by federation in production and marketing of wood and metal products and to evaluate marketing policy and programmes of apex federation. Five units were selected for study.